Rethinking theological training as ministerial empowerment for contextual mission: A case of the Uniting Presbyterian Church in Southern Africa - Sibusiso Zungu; Buhle Mpofu (HTS Teologiese Studies/Theological Studies, 2022)
This research engaged a realist paradigm to triangulate existing literature with data that emerged from a PhD study on ministerial formation within the context of being a missional church in the Uniting Presbyterian Church in Southern Africa (UPCSA). The study identified the need for theological training and ministerial formation to be relevant, contextual and responsive to the realities of the African communities. We concluded that current theological training module is dominated by Eurocentric expressions and narratives, which highlight an urgent need for a theological and ministerial formation model that will equip leaders with relevant and contextual missional strategies necessary for rapidly transforming African communities. There is a need for decolonisation and contextualisation of academic studies in order to align theological training and leadership development with the emerging challenges within the African context.